Effect of Ownership Structure on Financial Performance: Evidence from Listed Airlines in Africa - Jafari Makoka; Janeth Patrick Swai; Magwana Ngollo; Abraham Charles Nathanael (Universitas Airlangga, 2023)
Objective: This study empirically examines the impact of ownership structure on the financial performance of listed airlines in Africa. Design/Methods/Approach: The research utilized quantitative techniques to collect secondary data from listed airlines over ten years (2010-2019). Descriptive statistics and multiple regression were used for analysis. Findings: The results revealed that airlines with the majority of private domestic and private foreign ownership showed a significant positive effect on financial performance (ROA and ROE). In contrast, state ownership had an insignificant impact on airlines' financial performance. The study supports the property rights theory, emphasizing the importance of private ownership in airlines. Originality/Value: This study adds to the existing literature by providing evidence on how ownership structure influences financial performance in African airlines, contributing to aviation research. Practical/Policy Implication: The findings suggest that private and foreign investors should consider acquiring controlling airline stakes to enhance financial performance. Policymakers should aim to create flexible laws and regulations that attract domestic and foreign private investors to the aviation sector, potentially fostering improved management practices and policy developments.